Transferring Exome Sequencing Data from Clinical Laboratories to Healthcare Providers: Lessons Learned at a Pediatric Hospital - Swaminathan, Rajeswari; Huang, Yungui; Miller, Katherine; Pastore, Matthew; Hashimoto, Sayaka; Jacobson, Theodora; Mouhlas, Danielle; Lin, Simon (Frontiers in Genetics, 2018)
The adoption rate of genome sequencing for clinical diagnostics has been steadily increasing leading to the possibility of improvement in diagnostic yields. Although laboratories generate a summary clinical report, sharing raw genomic data with healthcare providers is equally important, both for secondary research studies as well as for a deeper analysis of the data itself, as seen by the efforts from organizations such as the American College of Medical Genetics and Genomics and the Global Alliance for Genomics and Health. Here, we aim to describe the existing protocol of genomic data-sharing between a certified clinical laboratory and a healthcare provider and highlight some of the lessons learned. This study tracked and subsequently evaluated the data transfer workflow for 19 patients, all of whom consented to be part of this research study and visited the genetics clinic at a tertiary pediatric hospital between April and December 2016. Two of the most noticeable elements observed through the study are the manual validation steps and the discrepancies in patient identifiers used by a clinical lab vs healthcare provider. Both of these add complexity to the transfer process as well as make it more susceptible to errors. Results from this study highlight some of the critical changes that need to be made in order to improve the genomic data sharing workflow between healthcare providers and clinical sequencing laboratories.